AGEs-RAGE manipulates tumor intrinsic pERK/Sp1/IL6 pathway and reprograms macrophage to promote intrahepatic cholangiocarcinoma progression - Juan Zhang; Biyang Jing; Xiaojian Ni; Youpei Lin; Jiaomeng Pan; MaoPei Chen; Boheng Zhang; Lan Zhang; Ningling Ge; Ruyuan Deng; Xiao Wang; Guohe Song (Translational Oncology, 2025)
Tumors often exhibit oxygen deprivation and enhanced glucose uptake, leading to glycolysis. Advanced glycation end products (AGEs) protein modifications induced by hyperglycemia—activate signaling pathways that promote cancer progression upon binding to its receptor (RAGE). In this study, AGEs-treatment enhanced the growth, invasion and migration of intrahepatic cholangiocarcinoma cells (ICC), while increasing IL-6 expression and secretion. Meanwhile, AGEs stimulated the expression of RAGE, specificity protein 1 (Sp1), and the phosphorylation of extracellular signal-regulated kinase (ERK) in a dose-dependent manner. However, these effects were attenuated by RAGE antibody blockade, RAGE knockdown, the ERK inhibitor U0126, or Sp1-specific siRNA. Furthermore, the supernatant of AGEs-treated RBE cells induced M2 polarization of THP-1 macrophages. Thus, AGEs promote ICC progression partly through the pERK/Sp1/IL-6 pathway and M2 macrophage polarization. These findings highlight underscore the role of the AGEs-RAGE axis in driving ICC progression via pERK/Sp1/IL-6 signaling.